Improved UV Photodetection of Terbium-doped NiO thin films prepared by cost-effective nebulizer spray technique. (1st June 2021) - Devi, M. Dharani; Juliet, A. Vimala; Hariprasad, K.; Ganesh, V.; Ali, H. Elhosiny; Algarni, H.; Yahia, I.S.
Abstract: In the present study, pure and Tb-doped NiO thin films (3 and 6%) were coated on glass substrates using the cost-effective nebulizer spray technique. Their structural, morphological, photoluminescence, and UV sensing properties have been reported. The structural studies confirm the polycrystalline cubic structure with (111) preferred orientation. The structural parameters such as crystallite size, dislocation density, and strain were estimated and a considerable variation with the Tb doping was also reported. Atomic force microscope (AFM) images displaying spherical grains of the samples and the grain size is increasing with Tb concentration. The energy dispersive X-ray (EDX) studies confirmed the elements of Ni, O and Tb in the deposited thin films. The bandgap values are decreasing with doping concentration and the lowest value was observed for the 3% Tb concentration. Photoluminescence (PL) spectra reveal a sharp emission peak at 370 nm and a defect peak at 484 nm, which are attributed to the near band emission and blue emission, respectievely. The UV photodetector parameters such as Responsivity, External quantum efficiency, and Detectivity of pure and doped samples were studied and their values are in the range of 0.12–0.24 AW -1, 37–79%, and 18.74 × 10 9 to 1.75 × 10 10 Jones, respectively. The maximum rise and decay times of 0.4 and 1.8 s, respectievely were observed for the 3% doped sample due to high grain size and reduced the trapping sites and hence improving the UV light photodetector performance. Highlights: NiO:Tb thin films (0, 3 and 6%) were coated on glass substrates using the cost-effective nebulizer spray technique. (PL) spectra reveal emission peaks at 370 nm and 484 nm, which are attributed to the near band emission and blue emission. Maximum Responsivity, EQE, and Detectivity of 0.24 AW -1, 79%, and 1.75 × 10 10 Jones, respectively observed for 3% Tb doped NiO film.